2021
DOI: 10.1073/pnas.2111946118
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 forms a trimer with HMGB1 and HDAC1 that modulates gene × environment interaction with asbestos

Abstract: Carriers of heterozygous germline BAP1 mutations (BAP1+/−) are affected by the “BAP1 cancer syndrome.” Although they can develop almost any cancer type, they are unusually susceptible to asbestos carcinogenesis and mesothelioma. Here we investigate why among all carcinogens, BAP1 mutations cooperate with asbestos. Asbestos carcinogenesis and mesothelioma have been linked to a chronic inflammatory process promoted by the extracellular release of the high-mobility group box 1 protein (HMGB1). We report that BAP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Studies revealed significantly higher total and acetylated high-mobility group box 1 blood levels in patients with mesothelioma and in asbestos-exposed patients, compared with healthy controls, but this test relies on Western blotting, which is not suitable for screening, whereas validation of mass spectrometry and enzymelinked immunosorbent assay has proved difficult. 63 Fibulin-3, encoded by the SPP1 gene, is an extracellular glycoprotein expressed in most tissues in the early embryonic stage, and it is selectively elevated in patients with mesothelioma. Ongoing studies elucidated possible reasons for inconsistent readings depending on the tube that the blood is harvested owing to FBLN3 proteoloysis.…”
Section: Screening For Mesotheliomamentioning
confidence: 99%
“…Studies revealed significantly higher total and acetylated high-mobility group box 1 blood levels in patients with mesothelioma and in asbestos-exposed patients, compared with healthy controls, but this test relies on Western blotting, which is not suitable for screening, whereas validation of mass spectrometry and enzymelinked immunosorbent assay has proved difficult. 63 Fibulin-3, encoded by the SPP1 gene, is an extracellular glycoprotein expressed in most tissues in the early embryonic stage, and it is selectively elevated in patients with mesothelioma. Ongoing studies elucidated possible reasons for inconsistent readings depending on the tube that the blood is harvested owing to FBLN3 proteoloysis.…”
Section: Screening For Mesotheliomamentioning
confidence: 99%
“…High levels of HIF-1α protein increase the susceptibility to ferroptosis in renal carcinoma cells [ 231 , 232 ]. Notably, the tumor suppressor BRCA1-associated protein 1 (BAP1) is involved in apoptosis and ferroptosis in different cancer cells [ 233 , 234 ]. It has been demonstrated the role of BAP1 in attenuating cancer development by provoking the ferroptosis event via solute carrier family 7-member 11 (SLC7A11) inhibition [ 235 ].…”
Section: Mitochondrial Dysfunction and Inflammation In Cvds And Cancermentioning
confidence: 99%
“…It is well-known that asbestos fibers induce mesothelial cell carcinogenesis through prolonged tissue damage, inflammation and repair, with various mechanisms being proposed as implicated in this carcinogenesis, including the induction of a pro-tumoral inflammation in the pleural cavity [82,96]. The high mobility group box 1 (HMGB1) protein released by mesothelial cells and macrophages after asbestos exposure promotes chronic inflammation [97] but also induces autophagy in mesothelial cells promoting their survival and malignant transformation [98]. Besides, carriers of the heterozygous germline BAP1 mutation can be affected by any cancer type, but they are mostly susceptible to asbestos carcinogenesis and develop mesotheliomas, a "preference" suggested to be attributed to the higher amounts of HMGB1 secreted by these mutant cells [97].…”
Section: Non-specific Pleuritismentioning
confidence: 99%
“…The high mobility group box 1 (HMGB1) protein released by mesothelial cells and macrophages after asbestos exposure promotes chronic inflammation [97] but also induces autophagy in mesothelial cells promoting their survival and malignant transformation [98]. Besides, carriers of the heterozygous germline BAP1 mutation can be affected by any cancer type, but they are mostly susceptible to asbestos carcinogenesis and develop mesotheliomas, a "preference" suggested to be attributed to the higher amounts of HMGB1 secreted by these mutant cells [97].…”
Section: Non-specific Pleuritismentioning
confidence: 99%